The problem of translating cultural elements in the novel “Memory of the Body” by Ahlam Mostaghanemi into Farsi: Comparative study for translation using theory of Vladimir Ivire - Afzali, Ali; Al-atabi, Raheem; Falaki, Zeinab (Al-Adab Journal, 2021)
Translation is one of the most important contemporary cultural issues. As the translator's mission is not limited to replacing vocabulary, it must form a bridge between the culture of "source language" and "target language" and create a rapprochement between the two cultures. One of the problems long faced by translators is obtaining the equivalent of elements that only exist in one culture and not the other. Cultural elements are concepts that exist in a language and do not exist in others. These cultural elements create a cultural gap between the people of the same language, which makes the task of the translator more complicated and difficult. This study, through the descriptive-analytical method and based on the Vladimir Ever model (1987), aims to study and criticize the way the cultural components present in the novel “Memory of the Body” are narrated by the Algerian novelist “Ahlam Mostaghanemi” and translated into Persian by the Iranian “Reza Ameri” However, there are still some complications and ambiguities in translating cultural elements. The results of the study indicate that the translator only benefits from the merging process, and this in turn has contributed to finding difficulties in transferring cultural concepts from the source community to the target community.